Role of Female Research at the Asociacion Mexicana de Cirugia General Annual Meeting: A Retrospective Analysis From 2013 to 2019 - Mejía-Fernández, Lorelí; Romero-Hernández, Fernanda; López-Ruiz, Ana; Lopez-Verdugo, Fidel; Sanchez-Garcia, Jorge; Martinez-Ordaz, Jose L.; Moreno-Paquentin, Eduardo; Lopez-Gavito, Elena (Frontiers in Surgery, 2022)
Background: Academic surgery has been a traditionally male-dominated field. Female contribution remains challenging. In Mexico, there is no published evidence regarding gender disparity in academic surgery. We aimed to analyze the female role in clinical research submitted to the Asociación Mexicana de Cirugía General (AMCG). Methods: Retrospective study evaluating abstracts submitted to AMCG annual meetings from 2013 to 2019. Categorical variables were compared using 𝜒2 test. Univariate logistic regression was performed to calculate odds ratios (OR) followed by a log-binomial logistic regression model to obtain the adjusted relative risk (aRR) for acceptance as an oral presentation. Results: Overall, 7,439 abstracts were analyzed of which 24.2% were submitted by females. Female-submitted abstracts increased from 22.5% to 25.3% during 2013-2019 (p=0.15). The proportion of abstracts submitted by females was higher in the resident group (27.7% vs. 18.8%; p<0.001). The percentage of females’ abstracts selected for oral presentation was less than the percentage of males’ abstracts selected for presentation (9% vs. 11.5%; p=0.002). Females' abstracts submitted have a 23.5% decreased chance of being selected for oral presentation (OR=0.765, CI 95%: 0.639-0.917, p=0.003). However, after adjusting for research type and trainee status, the gender of the oral presenting author showed no association (aRR=0.95, CI95%: 0.8-1.1, p=0.56). Conclusion: In Mexico, the female role in academic surgery is still limited. These results should encourage professors and program directors to identify and address factors contributing to gender disparities.